2016
DOI: 10.1371/journal.pone.0150069
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Performance of NoSQL Approaches for Managing Archetype-Based Electronic Health Record Data

Abstract: This study provides an experimental performance evaluation on population-based queries of NoSQL databases storing archetype-based Electronic Health Record (EHR) data. There are few published studies regarding the performance of persistence mechanisms for systems that use multilevel modelling approaches, especially when the focus is on population-based queries. A healthcare dataset with 4.2 million records stored in a relational database (MySQL) was used to generate XML and JSON documents based on the openEHR r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
(16 reference statements)
1
23
0
Order By: Relevance
“…The new KV data model implemented on HBase exhibited an average 5.24-fold increase in high-dimensional biological data query performance compared to the relational model implemented on MySQL Cluster and an average 6.47-fold increase on query performance on MongoDB [22]. Freire et al, [40] showed highest performance of CouchDB (similar to MongoDB and document store model) but required much more disk space and longer indexing time compared to other KV stores. The performance evaluation found that KV data model, in particular its implementation in HBase, outperforms and, therefore, supports this studies use of NoSQL technology for large-scale BDA platform for a hospital system.…”
Section: Discussionmentioning
confidence: 99%
“…The new KV data model implemented on HBase exhibited an average 5.24-fold increase in high-dimensional biological data query performance compared to the relational model implemented on MySQL Cluster and an average 6.47-fold increase on query performance on MongoDB [22]. Freire et al, [40] showed highest performance of CouchDB (similar to MongoDB and document store model) but required much more disk space and longer indexing time compared to other KV stores. The performance evaluation found that KV data model, in particular its implementation in HBase, outperforms and, therefore, supports this studies use of NoSQL technology for large-scale BDA platform for a hospital system.…”
Section: Discussionmentioning
confidence: 99%
“…Moniruzzaman, S.A. Hossain [22]; S. Sharma, R. Shandilya, S. Patnaik, et al [23]; S.M. Freire, D. Teodoro, F. Wei-Kleiner, et al [24], we used the NoSQL approach to develop the PPD information storage layer. In our reasoning, we also started from the fact that there is another advantage of the NoSQL, which is very important for the scalability of the entire system.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Into the researches [8]- [10] are analyzed the MongoDB, NoSQL databases and reasoning behind choose of them, query optimizations, and comparisons between NoSQL and SQL databases are shown. [11], analyze the MongoDB clusters and introduce how to partition spatial data to distributed nodes in the parallel environment, using its spatial relationships between features.…”
Section: Related Workmentioning
confidence: 99%